Budidaya Pakchoy (Brassica rapa L.) di Lahan Tailing Pasir Bekas Penambangan Timah dengan Amelioran Pupuk Organik dan Pupuk NPK - I. Inonu; N. S. Khodijah; A. Supriadi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
The objectives of this research are to study of the feasibility of using the sandy tailings for pakchoy (Brassica rapa L.) cultivation, to study the effect of organic manure and NPK fertilizer ameliorants to growth and yield of pakchoy and to get the optimum dosage of the organic manure and NPK fertilizer for pakchoy cultivation in sandy tailings of tin post-mining. This research was conducted in sandy tailings site which has been 27th years old after mining in Pemali Village Bangka District on May 2013 to July 2013. This research used factorial randomized completely block design with two factors and three replications. The first factor is organic manure dosage (15; 30; 45 ton/ha) and the second one is NPK fertilizer dosage (200; 250; 300 kg/ha).The results that the sandy tailings of tin post-mining is feasible to pakchoy cultivation. Organic manure dosage affected the growth and production of pakchoy and dosage of 30 ton/ha of organic fertilizer give the best growth and yield responses. There was no significant effect of NPK dosage to growth and yield of pakchoy. There was no significantly interaction effect of organic manure and NPK factors to growth and yield of pakchoy.